2016
DOI: 10.5713/ajas.15.0812
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carcass Characteristics, Meat Quality, and Blood Parameters of Slow and Fast Grown Female Broiler Chickens Raised in Organic or Conventional Production System

Abstract: The objective of the study was to compare the carcass characteristics, meat quality, and blood parameters of slow and fast grown female broiler chickens fed in organic or conventional production system. The two genotypes tested were medium slow-growing chickens (SG, Hubbard Red JA) and commercial fast-growing chickens (FG, Ross 308). Both genotypes (each represented by 400 chickens) were divided into two sub-groups fed either organic (O) or conventional (C) systems. Chickens of each genotype and system were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 16 publications
2
30
0
8
Order By: Relevance
“…Similar to us, Michalczuk et al (2017) reported lower levels of SFA in the breast meat of slowgrowing chickens reared outdoors on pasture when compared to the indoors system, however they observed higher MUFA content in the pastured chickens. Cömert et al (2016) observed increased content of SFA and MUFA in the drumstick of both fast and slow-growing chicken genotypes when reared in organic system with pasture access compared to conventional system, and also surprisingly reported decreased content of the ω-6 and ω-3 PUFA in the chickens from the pastured groups. This contradicts to our results concerning the contents of SFA, MUFA and PUFA.…”
Section: Resultsmentioning
confidence: 92%
“…Similar to us, Michalczuk et al (2017) reported lower levels of SFA in the breast meat of slowgrowing chickens reared outdoors on pasture when compared to the indoors system, however they observed higher MUFA content in the pastured chickens. Cömert et al (2016) observed increased content of SFA and MUFA in the drumstick of both fast and slow-growing chicken genotypes when reared in organic system with pasture access compared to conventional system, and also surprisingly reported decreased content of the ω-6 and ω-3 PUFA in the chickens from the pastured groups. This contradicts to our results concerning the contents of SFA, MUFA and PUFA.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Poltowicz and Doktor (2011) showed that free range with pasture decreased the live weight in the chickens, but only in the male ones. On the other hand, Cömert et al (2016) observed significantly higher live weight in fast-growing chickens, reared outdoors, but no effect of the rearing system in slow-growing lines. Our results are in line with Wang et al (2009) who reported lower live weight in slow-growing chickens reared free-range with access to grass paddocks and Li et al (2017) in medium -growing chickens raised indoors on floor and outdoors with pasture.…”
Section: Carcass Traitsmentioning
confidence: 69%
“…One of the major goals in the poultry meat industry is to reduce the carcass fatness and mainly the deposition of the abdominal fat (Fouad and El-Senousey, 2014). Jiang et al (2011) and Li et al (2017) found significant decrease in the abdominal fat as a result of the pasture rearing, while Cömert et al (2016) observed generally increased abdominal fat in outdoor reared lines, more pronounced in the fast growing ones. No effect of pasture was detected on the percentage of the deposited abdominal fat in our study, which is in agreement with the results of Mikulski et al (2011) and Chen et al (2013).…”
Section: Carcass Traitsmentioning
confidence: 97%
See 1 more Smart Citation
“…Concomitant with this interest in slower growing chickens for meat is an emerging scientific literature on production systems (e.g. Fanatico et al 2015;Comert et al 2016;Stadeg et al 2017) and meat quality (e.g. De Marchi et al 2005;Fanatico et al 2007) of these chickens.…”
Section: Introductionmentioning
confidence: 99%